2004
DOI: 10.5741/gems.40.1.26
|View full text |Cite
|
Sign up to set email alerts
|

Cultured Pearls from the Gulf of California, Mexico

Abstract: Black pearls have been found in Mexico's Gulf of California since the area was settled more than 2,000 years ago. Attempts at culturing pearls in this area have met with varying success over the past century. Today, a pearl farm in Guaymas is producing commercial quantities of mabe as well as bead-nucleated full-round cultured pearls from the indigenous pearl oyster Pteria sterna. This article provides an overview of the history of natural and cultured pearls from Mexico, describes pearl culturing at the Guaym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
12

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 15 publications
(20 reference statements)
2
38
0
12
Order By: Relevance
“…In addition, there are spectroscopic variations among geographic sources of "black" cultured pearls. For example, the 661-694 nm band, which we observed consistently in our Tahitian cultured pearls, was not reported in Mexican cultured pearls (Kiefert et al, 2004), even though they showed very similar coloration. The presence of these bands provides a good indication for substantial quantities of organic components.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…In addition, there are spectroscopic variations among geographic sources of "black" cultured pearls. For example, the 661-694 nm band, which we observed consistently in our Tahitian cultured pearls, was not reported in Mexican cultured pearls (Kiefert et al, 2004), even though they showed very similar coloration. The presence of these bands provides a good indication for substantial quantities of organic components.…”
Section: Discussionmentioning
confidence: 61%
“…Various organic components occur between the aragonite platelets, producing a range of pearl colors (e.g., Kiefert et al, 2004;Strack, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, the presence of these substances is detected at 390 to 425 nm, depending on the specific structure in a species (Britton 1990). Although Kiefert et al (2004) reported the presence of porphyrins in P. sterna at 400 to 405 nm, we only observed them with a blue-light filter in the range of 330 to 385 nm, and not at 450 to 480 nm.…”
Section: Discussionmentioning
confidence: 64%
“…Yet, pearl farming remains an interesting craft for local communities, as it has the potential to create a sustainable development in remote coastal areas (Cartier and Ali 2012). Commercially operating pearl farms are now located in the Pacific (French Polynesia, Cook Islands, Fiji, Micronesia), Australia, Indonesia, the Philippines, Vietnam, Thailand, Myanmar, the Arabian Gulf, Sudan (Red Sea), Tanzania, and even in Baja California, Mexico (Kiefert et al 2004;Brown 2005;Southgate et al 2006;Strack 2006;Southgate and Lucas 2008;Müller 2009;). …”
Section: Pearling History and Related Problems For Pearl Identificationmentioning
confidence: 99%